2022
DOI: 10.4236/aim.2022.127030
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Brucellosis in Cameroon: Diagnostic Approaches, Epidemiology and Risk Factors for Infection

Abstract: Brucellosis is a neglected tropical zoonotic disease that threatens the food production and public health sectors. It is of considerable animal welfare and economic importance and is underreported in most parts of the world, especially in developing countries like Cameroon. Brucellosis has been reported in cattle, other domestic animals and humans in Cameroon. The burden of the disease is unclear, and the awareness remains questionable. It became necessary for this review to be carried out to highlight the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 88 publications
0
6
0
2
Order By: Relevance
“…By sequencing, it is possible to discover molecular mechanisms that explain variations of biotypes and evolutionary relationships for human brucellosis [ 148 , 149 ]. Identifying these targets could be a significant step forward in the development of diagnoses and vaccinations aimed at combating and treating brucellosis [ 150 ].…”
Section: Diagnostic Approaches Of Zoonotic Brucellosismentioning
confidence: 99%
See 1 more Smart Citation
“…By sequencing, it is possible to discover molecular mechanisms that explain variations of biotypes and evolutionary relationships for human brucellosis [ 148 , 149 ]. Identifying these targets could be a significant step forward in the development of diagnoses and vaccinations aimed at combating and treating brucellosis [ 150 ].…”
Section: Diagnostic Approaches Of Zoonotic Brucellosismentioning
confidence: 99%
“…In low-income countries, the current availability of next-generation sequencing technologies is woefully insufficient to meet the requirements for research carried out in those countries. The fact that there is no specific test for definitively identifying a bacterium is the primary reason for the necessary integration of multiple techniques for Brucella’ s diagnosis [ 149 , 151 , 152 ]. Although there are valid and reliable advertising and home-made molecular techniques that can ensure a high degree of accuracy and precision of results, conventional methods of culture and indirect methods of serology continue to be the primary methods of diagnosing brucellosis and following up on infections caused by Brucella species.…”
Section: Diagnostic Approaches Of Zoonotic Brucellosismentioning
confidence: 99%
“…Brucellosis, caused by a group of bacteria of the genus Brucella, is a widespread, endemic, and neglected zoonotic disease in most low-income countries [1,2]. Te genus Brucella includes twelve species, some of which are hostspecifc [3,4]. Te disease afects both humans and domestic animals, particularly cattle [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Tis difculty has been mainly due to the uncontrolled movement of diseased animals (mainly cattle) within and outside the national territory [6]. In addition, there is no surveillance system for detecting and slaughtering to eliminate infected cattle from the herds [4,18]. A review of the literature on brucellosis research in Cameroon revealed that no study has been conducted in regions experiencing the urbanisation of cattle from the regions reported to be endemic for the disease [4,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation